INNOVATIVE TECHNOLOGIES IN THE ORGANIZATION OF THE EDUCATIONAL PROCESS IN HIGHER EDUCATION - Bruyaka , Olga (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
In the article, an overview of the possibilities and prospects for using innovative methods in the context of studying physics is presented, particularly in the process of working with students in the preparatory department.